FOLIAR SPRAYING OF DOSES OF BORIC ACID IN CORIANDER (Coriandrum sativum L.) - Jéssica Rodrigues de Mello Duarte; Scarlet de Aguiar Basílio; Isabela Carolina Silva; Elaine Gleice Silva Moreira; Adilson Pelá (Revista de Agricultura Neotropical, 2020)
Coriander (Coriandrum sativum) is a species highly appreciated in Brazilian cuisine and of high nutritional importance due to the presence of vitamins, calcium, and iron. Leafy vegetables are considered nutritionally demanding as their cycles are relatively short and the lack of any essential element affects their growth, yield and quality. This study aimed to evaluate the response of coriander plants (Coriandrum sativum L.) to foliar spraying of boron doses. The experiment was carried out in a greenhouse at The State University of Goiás, Campus Ipameri, in Ipameri-GO. The experimental design was completely randomized, with five treatments and four replications. The treatments consisted of five boron doses applied by foliar spray (0, 1.0, 1.5, 2.0 and 3.0 kg ha-1) using boric acid (17% of Boron) as the source. Fresh and dry matter of shoot and root and leaf boron contents were evaluated. Data were subjected to analysis of variance (F test) and the effect of boron doses were evaluated by regression analysis. The application of 3.0 kg ha-1 of boron increases the boron content of coriander plants, and the fresh and dry matter of roots and shoots was not significantly increased.